Crosstalk between mesenchymal stem cells and T regulatory cells is crucially important for the attenuation of acute liver injury. Issue 5 (16th April 2018) - Gazdic, Marina; Markovic, Bojana Simovic; Arsenijevic, Aleksandar; Jovicic, Nemanja; Acovic, Aleksandar; Harrell, C. Randall; Fellabaum, Crissy; Djonov, Valentin; Arsenijevic, Nebojsa; Lukic, Miodrag L.; Volarevic, Vladislav
Abstract : One of the therapeutic options for the treatment of fulminant hepatitis is repopulation of intrahepatic regulatory cells because their pool is significantly reduced during acute liver failure. Although it is known that mesenchymal stem cells (MSCs), which have beneficent effects in the therapy of fulminant hepatitis, may promote expansion of regulatory T cells (Tregs) and regulatory B cells (Bregs), the role of these regulatory cells in MSC‐mediated attenuation of acute liver injury is unknown. Herewith, we described the molecular mechanisms involved in the crosstalk between MSCs and liver regulatory cells and analyzed the potential of MSC‐based therapy for the expansion of intrahepatic regulatory cells in mouse model of acute liver failure. MSC‐dependent attenuation of α‐galactosylceramide (α‐GalCer)–induced acute liver injury in mice was accompanied with an increased presence of interleukin (IL) 10–producing CD4 + CD25 + forkhead box P3 + Tregs and IL10– and transforming growth factor β–producing marginal zone–like Bregs in the liver. Depletion of Bregs did not alter MSC‐based alleviation of acute liver failure, whereas depletion of Tregs completely abrogated hepatoprotective effects of MSCs and inhibited their capacity to attenuate hepatotoxicity of liver natural killer T cells (NKTs), indicating that Tregs, and not Bregs, were critically involved in MSC‐based modulation of acute liver inflammation. MSCs, in a paracrine, indoleamine 2, 3‐dioxygenase–dependent manner, significantly increased the capacity of Tregs to produce immunosuppressive IL10 and to suppress hepatotoxicity of liver NKTs. Accordingly, adoptive transfer of MSC‐primed Tregs resulted in the complete attenuation of α‐GalCer–induced acute liver failure. In conclusion, our findings highlighted the crucial importance of Tregs for MSC‐based attenuation of acute liver failure and indicated the significance of MSC‐mediated priming of Tregs as a new therapeutic approach in Treg‐based therapy of acute liver injury. Liver Transplantation 24 687–702 2018 AASLD.